2011
DOI: 10.1111/j.1365-2966.2011.18968.x
|View full text |Cite
|
Sign up to set email alerts
|

Global asteroseismic properties of solar-like oscillations observed by Kepler: a comparison of complementary analysis methods

Abstract: We present the asteroseismic analysis of 1948 F‐, G‐ and K‐type main‐sequence and subgiant stars observed by the National Aeronautics and Space Administration Kepler mission. We detect and characterize solar‐like oscillations in 642 of these stars. This represents the largest cohort of main‐sequence and subgiant solar‐like oscillators observed to date. The photometric observations are analysed using the methods developed by nine independent research teams. The results are combined to validate the determined gl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
109
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 111 publications
(116 citation statements)
references
References 59 publications
7
109
0
Order By: Relevance
“…We measured 74.9 ± 0.4 μHz. Other methods, similar to those used by Verner et al (2011), converge on the same value. Comparison of different methods has shown that the EACF provides reliable results.…”
Section: Mean Seismic Global Parametersmentioning
confidence: 90%
See 2 more Smart Citations
“…We measured 74.9 ± 0.4 μHz. Other methods, similar to those used by Verner et al (2011), converge on the same value. Comparison of different methods has shown that the EACF provides reliable results.…”
Section: Mean Seismic Global Parametersmentioning
confidence: 90%
“…This means that there are a large number of main-sequence stars and subgiants that can serve as seismic references. We consider that an EACF of 100 is enough for the reference, so that we currently identify more than 80 possible references for subgiants and main-sequence stars, according to previous CoRoT and Kepler observations (e.g., Verner et al 2011). The only domain where the set of reference stars appears to be loose in the main sequence for stars with a lower mass than the Sun is for ν max ≥ 3.6 mHz.…”
Section: Choosing a Referencementioning
confidence: 99%
See 1 more Smart Citation
“…It relies on a global description of the oscillation spectrum, which considers that the mean values of the seismic parameters are determined in a large frequency range around ν max ). Such a description has shown interesting properties when compared to a local one that provides the large separation from a limited frequency range only around ν max (Verner et al 2011;Hekker et al 2012). It is straightforward to make the link between both asymptotic and observed descriptions of the radial oscillation pattern with a second-order development in (n − n max )/n max of the asymptotic expression.…”
Section: Taking Into Account the Curvaturementioning
confidence: 99%
“…This mass interval exhibits a large range of the physical properties of convective envelopes (such as the depth, physical size, mass, and density), as well as in the overall stellar luminosity transported by convection. These types of stars are also targets for asteroseismic studies (e.g., Verner et al 2011), which have the potential to give precise measurements of stellar properties for large numbers of stars. The goal here is to determine how the convection, differential rotation, and meridional circulation is influenced by stellar mass, and to see if general trends or scaling laws can be extracted that will guide a deeper understanding of the inner hydrodynamics of these stars.…”
Section: Introductionmentioning
confidence: 99%